1993
DOI: 10.1104/pp.102.3.789
|View full text |Cite
|
Sign up to set email alerts
|

Chromoplast-Targeted Proteins in Tomato (Lycopersicon esculentum Mill.) Fruit

Abstract: The chloroplast to chromoplast transition during tomato (Lycopersicon esculenfum Mill.) fruit ripening i s characterized by a dramatic change in plastid structure and function. We have asked whether this process is mediated by an increase in the steady-state leve1 of RNA for plastid targeted proteins. Assays for import of radiolabeled translation products into isolated pea (Pisum safivum 1.) chloroplasts were used to monitor levels of chromoplasttargeted proteins at four stages of tomato fruit development. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…We suggest that the most probable cleavage site for the melon PSY is after or near the 83rd amino acid. Cleavage in this region would generate a mature PSY of 38 kDa which is in agreement with the estimated size for the PSY from tomato either by immunoblotting [12] or by import assays with heterologous systems [4,22]. It has been observed that there is stronger conservation among the amino acid sequences of transit peptides encoded by the same gene from different plants than among those encoded from different genes of the same plant [29].…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…We suggest that the most probable cleavage site for the melon PSY is after or near the 83rd amino acid. Cleavage in this region would generate a mature PSY of 38 kDa which is in agreement with the estimated size for the PSY from tomato either by immunoblotting [12] or by import assays with heterologous systems [4,22]. It has been observed that there is stronger conservation among the amino acid sequences of transit peptides encoded by the same gene from different plants than among those encoded from different genes of the same plant [29].…”
Section: Discussionsupporting
confidence: 66%
“…These cleavage sites would generate tomato PSY proteins that are much smaller than those actually observed. The import studies of Lawrence et al [22] suggest that the tomato PSY may be cleaved to a 41 kDa protein. Import assays with heterologous systems have not proved to be absolutely reliable for correct proces sing of mature proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They suggested that the most probable cleavage site for the MEL5 is after or near the 83rd amino acid, which corresponds to the 90th amino acid in our CitPSY1. Although there has been no available protein information on citrus PSY, the position of the 90th amino acid is based on the estimated size of tomato PSY (Bartley et al 1992; Lawrence et al 1993; Fraser et al 1994). However, taking into consideration that the size of mature polypeptides were predicted based on comparisons with the bacterial (33.0 kDa) and cyanobacterial (35.7 kDa) orthologs of PSY (Chamovitz et al 1992), the possibility can not be excluded that the location of the cleavage site might be at the 153rd amino acid or at another site at around the 125th amino acid.…”
Section: Discussionmentioning
confidence: 99%
“…• Several ripening-related cDNAs have homology to cloned mRNAs which also accumulate during stressrelated processes. TOM 66, TOM 111 and TOM 129 are homologous to low molecular weight heat shock proteins (Fray, Lycett & Grierson 1990;Lawrence, Cline & Moore 1993;Picton et al 1993a respectively). It is not known why these genes are active during fruit ripening.…”
Section: Functional Characteristics Of Genesmentioning
confidence: 99%